THE QUALITY OF INDONESIAN - ENGLISH TRANSLATION BY ENGLISH DEPARTMENT STUDENTS OF HIGHER LEARNING INSTITUTIONS IN MAKASSAR - Mansur Akil (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2011)
ABSTRACTS The study aims at describing the quality aspects of Indonesian-English translation made by English department students of higher institutions in Makassar. The population of this research is English Department students of higher learning institutions in Makassar. The target population subjects were all students majoring in English in both state and institutions in Makassar totaling about 3750. While the accessible population subjects only the students who went to the five selected institutions, namely UNHAS, UNM, UMI, UNISMUH, and ABA ATMAJAYA, about 2646. This research applied two-staged sampling procedure by combining purposive and random sampling method. Purposive sampling was used to determine the higher learning institutions and semester of the students, the criteria for this was the well established higher learning institutions of both non-education and education based and the fifth semester up or the students who had completed at least 80 credits (sks) and had attended translation class at least Translation I or Theory of Translation Class. The number of students meeting the requirements out of the 2646 was about 897. This was randomly sampled. The sample size was based on Morgan table. The result of the study shows that the quality of the students’ translations, therefore, was very poor; the average grade was only 0.65 on (0-4) grading scale. All aspects (accuracy, clarity, and naturalness) were poor and varied by institutions, by status of institutions, and by semester: The translation among higher learning institutions were UNM 0.96, UNHAS 0,84, ABA ATMAJAYA 0.69, UMI 0.58, and UNISMUH 0.20, the state 0.92 and the non-state 0.46, semester V 0.46 and semester VII 0.89. This implies that different education and different experience the students got from their institutions will differentiate the quality of their translations. This is supported by the facts that the grades of certain institutions were higher than that of the other, the grades of state institutions were higher than that of the non-state institutions, the grades of the higher semester was better than that of the lower semester and, it is interesting to highlight here that ABA ATMAJAYA has the highest translation quality among the non-state higher institutions involved in this study, why? The answer to this question will vary according to the objective conditions in each higher learning institutions.